(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Ultrasound is reported superior to clinical palpation for detecting lymph nodes and metastasis. The advantage of ultrasound over other imaging modalities is price, low patient burden, and possibilities for follow up. A cross sectional Study on 29 cases of oral squamous cell carcinoma was done in Department of Oral & Maxillofacial Surgery, Dhaka Dental College & Hospital, Dhaka from January 2006 to December 2007. The sensitivity, specificity, positive predictive value, negative predictive value & Accuracy of Ultrasonographic technique for determining metastatic cervical lymph node were 93.33%, 50%, 66.7%, 87.5% and 72.4% respectively. Considering the finding of the study, Sonographic evaluation can improve the diagnosis of metastatic cervical lymph node in patients with oral squamous cell carcinoma. It is cost effective, non-invasive, less burden to patient, does not create problem of overlapping with mandible and can be done repeatedly to follow up. Therefore, high resolution sonography may be an adjunct tool in diagnosing metastatic nodes in patients with oral squamous cell carcinoma. DOI: 10.3329/jbcps.v28i2.5369 J Bangladesh Coll Phys Surg 2010; 28: 92-99